Regulating the doom loop - Spyros Alogoskoufis; Sam Langfield (European Central Bank (ECB), 2019)
Euro area governments have committed to break the doom loop between banks and sovereigns. But policymakers disagree on how to treat sovereign exposures in bank regulation. Our contribution is to model endogenous sovereign portfolio reallocation by banks in response to regulatory reform. Simulations highlight a tension between concentration and credit risk in portfolio reallocation. Resolving this tension requires regulatory reform to be complemented by an expansion in the portfolio opportunity set to include an area-wide low-risk asset. By reinvesting into such an asset, banks would reduce both their concentration and credit risk exposure.
Keywords: G01; G11; G21; G28; 330; Bank regulation; sovereign risk; systemic risk